A STUDY OF NUMERICAL METHODS FOR FLOWS IN CHANNELS (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
Channel flows are a critical subject in fluid dynamics with wide-ranging applications in engineering, environmental studies, and industrial processes. Numerical methods have become indispensable tools for analyzing these flows due to the complexity of governing equations and boundary conditions. This paper presents a comprehensive study of numerical methods applied to channel flows, including finite difference, finite volume, and finite element methods. We discuss the theoretical foundations, implementation details, and comparative performance of these methods in solving channel flow problems.